Optimized layout of supporting facilities in mountainous industrial parks: a case study of Chongqing Dadi Industrial Park - Duan, Ran; Tang, Rui; Wang, Zhigang; Yang, Jiyi; Su, Jiafu (Frontiers in Ecology and Evolution, 2023)
The establishment of industrial parks has become a pivotal driver of urban economic growth in China, particularly given that around 69% of the country's landmass is covered by mountains. Consequently, the development of industrial parks in mountainous urban areas holds immense significance. A critical aspect of steering industries toward high-quality development lies in strategically arranging supporting facilities within these industrial parks. However, the intricate topography of mountainous regions introduces challenges in devising effective layouts for such facilities within these parks. This article takes a user-centric perspective to examine the relationship between mountainous terrain and user fatigue. By applying equivalent coefficient methods, we establish a correlation between undulating paths in mountainous terrain and flat paths. This correlation serves as the foundation for a visual analytical, designed to facilitate the rational placement of supporting facilities in mountainous industrial parks. Empirical validation of our approach is achieved through the analysis of the supporting facility layout at Chongqing Dadi Industrial Park. The insights gleaned from our study provide a basis for optimizing the supporting facilities and the planning of such industrial parks. In conclusion, our research yields dual benefits: firstly, a scientific framework for guiding the rational layout of supporting facilities, and secondly, practical insights into the comprehensive planning and design of mountainous industrial parks. By enhancing user experiences and aligning with urban growth trajectories, our research emerges as a valuable resource for the advancement of mountainous industrial parks.